Obstetric and Perinatal Outcomes After Assisted Reproductive Technology in Women With Cesarean Scar - Lin, Yue; Chen, Qianqian; Huang, Xuefeng; Wang, Ziliang; Chen, Cuie; Chen, Haiying; Jin, Fan (Frontiers in Physiology, 2022)
Introduction: Assisted reproductive technology (ART) and previous Cesarean section (CS) are independently associated with the risk of adverse obstetric and perinatal outcomes in general. Few studies have focused on the association between adverse obstetric and perinatal outcomes and ART used in the high-risk population of women with previous CS. Materials and methods: A retrospective cohort study including 14,099 women with a previous delivery and a subsequent delivery between April 2014 and April 2020 was conducted at our hospital. We assessed the risk of adverse obstetric and perinatal outcomes in pregnancies conceived by ART in women with previous CS, using log-binomial regression models. Results: In women with previous CS, ART singleton pregnancies were associated with an increased risk of maternal complications, such as pregnancy complications, placental anomalies of implantation, postpartum hemorrhage, and preterm birth (PTB), as compared to spontaneously conceived pregnancies. The implementation of ART and previous CS interacted in a synergistic manner to increase the likelihood of the placenta accreta spectrum in women with singleton pregnancies (adjusted relative risk [aRR] 5.30, 95% confidence interval [CI] 4.01‒7.00; relative risk due to interaction: 1.41, 95%CI 0.07‒2.75). In women with previous CS who underwent ART, women with singletons conceived through intracytoplasmic sperm injection were at increased risk of velamentous placenta (aRR 2.46, 95%CI 1.35-4.48) compared with those with singletons conceived through in vitro fertilization (IVF), whereas women with singletons conceived through cleavage-stage embryo transfer (ET) were at increased risk of gestational diabetes mellitus (aRR 1.74, 95%CI 1.16‒2.60) than those with singletons conceived through blastocyst-stage ET. Conclusions: Pregnancies conceived through ART were at increased risk for adverse obstetric and perinatal outcomes in women who had previously delivered by CS, particularly for placental anomalies of implantation. In women with previous CS undergoing ART, IVF and blastocyst-stage ET may be a relatively safe treatment.